Consuming dance choreography and advertising - Dunagan, Colleen T. 1971- (New York, NY Oxford University Press, 2018)
Whether advertising clothes or technology, dance is a staple of advertising today. Consuming Dance offers a clear history and analysis of dance in advertising and demonstrates the ways in which the form articulates with, informs, and reflects U.S. culture
Dance-in-advertising, affect, and contagious movement -- Commercials as discursive assemblages -- Correspondence and difference : creating rapport through intertextuality -- Consumer culture and appropriation : advertising, dance, and social identity -- Subjectivity and performative consumption.
"Visit companion website at www.oup.com/us/consumingdance" --back cover
Includes bibliographical references and index
Keywords: Dance in motion pictures, television, etc. -- History; Television advertising -- History